Broadly Immunogenic HLA Class I Supertype-Restricted Elite CTL Epitopes Recognized in a Diverse Population Infected with Different HIV-1 Subtypes - Perez, Carina L; Larsen, Mette V; Gustafsson, Rasmus; Norstrom, Melissa M; Atlas, Ann; Nixon, Douglas F; Nielsen, Morten; Lund, Ole; Karlsson, Annika C (The Journal of immunology (1950), 2008)
The genetic variations of the HIV-1 virus and its human host constitute major obstacles for obtaining potent HIV-1-specific CTL responses in individuals of diverse ethnic backgrounds infected with different HIV-1 variants. In this study, we developed and used a novel algorithm to select 184 predicted epitopes representing seven different HLA class I supertypes that together constitute a broad coverage of the different HIV-1 strains as well as the human HLA alleles. Of the tested 184 HLA class I-restricted epitopes, 114 were recognized by at least one study subject, and 45 were novel epitopes, not previously described in the HIV-1 immunology database. In addition, we identified 21 “elite” epitopes that induced CTL responses in at least 4 of the 31 patients. A majority (27 of 31) of the study population recognized one or more of these highly immunogenic epitopes. We also found a limited set of 9 epitopes that together induced HIV-1-specific CTL responses in all HIV-1-responsive patients in this study. Our results have important implications for the validation of potent CTL responses and show that the goal for a vaccine candidate in inducing broadly reactive CTL immune responses is attainable.